Exploring the Students' Difficulties in Understanding Reading Texts at the Tenth Grade of SMK Syabilrosyad NW Semaya in Academic Year 2022/2023: Exploring the Students' Difficulties in Understanding Reading Texts at the Tenth Grade of SMK Syabilrosyad NW Semaya in Academic Year 2022/2023 - dzoharat nabilah (Innovative Pedagogy and Education Studies, 2024)
Reading comprehension is an essential skill in English language learning, yet many students still experience difficulties in understanding reading texts. This study aims to explore the students’ difficulties in understanding reading texts at the tenth grade of SMK Syabilrosyad NW Semaya in the academic year 2022/2023. The research employed a descriptive qualitative approach. The participants were tenth-grade students selected through purposive sampling. Data were collected through reading tests, questionnaires, and interviews. The findings revealed that students faced several difficulties, including limited vocabulary mastery, lack of background knowledge, difficulty in identifying main ideas and specific information, and problems in understanding text structure. Additionally, students’ low motivation and limited reading strategies also contributed to their comprehension problems. The study concludes that these difficulties hinder students’ reading performance and suggests that teachers apply appropriate teaching strategies, such as vocabulary enrichment and explicit reading strategy instruction, to improve students’ reading comprehension skills.